Komparasi Metode Single Moving Average dan Double Exponential Smoothing untuk Peramalan Penjualan Produk Gerabah pada UD. Amerta Sedana - Christina Purnama Yanti; Ni Luh Wiwik Sri Rahayu Ginantra; Dewa Ayu Putri Wulandari; Ni Putu Adelia Indah Paramita (JURIKOM (Jurnal Riset Komputer), 2022)
One of the areas producing creative industries in Bali is Tabanan Regency which produces creative industries in the form of pottery. In the community, earthenware products are usually known in the form of objects that function as containers, for example flower vases, pots, barrels, jugs, jars and so on. Sales of pottery products at the UD company. Amerta Sedana every month experiences erratic fluctuations. In planning sales, the company only estimates the number of sales without using the scientific method as a benchmark to assist the company in determining the next sales. This causes the company to be unable to maximize sales for the following month and fulfill consumer demand for goods. One solution that can be used is to do forecasting. Forecasting is a picture of the state of the company in the future and this picture is very important for the company. There are various types of methods that can be used to perform forecasting calculations. This study uses a comparison of the Single Moving Average and Double Exponential Smoothing methods for forecasting sales of small pot number 1, pot lion white, and pot monkey. The results showed that the calculation with the smallest error value was the sale of small pot number 1 with the 2-month Single Moving Average method with an MSE value of 56.1 and an MAD value of 4.942857, a lion white pot with a 2-month Single Moving Average method with an MSE value of 707.3214. and the MAD value is 18.82857, the monkey pot uses the 2-month Single Moving Average method with a value of 247.8786 and a MAD value of 11.32857